2023
DOI: 10.1038/s41598-023-42994-2
|View full text |Cite
|
Sign up to set email alerts
|

NOXA expression is downregulated in human breast cancer undergoing incomplete pathological response and senescence after neoadjuvant chemotherapy

Sofian Al Shboul,
Mohammed El-Sadoni,
Ahmad Alhesa
et al.

Abstract: Neoadjuvant chemotherapy (NAC) is a frequently utilized approach to treat locally advanced breast cancer, but, unfortunately, a subset of tumors fails to undergo complete pathological response. Apoptosis and therapy-induced senescence (TIS) are both cell stress mechanisms but their exact role in mediating the pathological response to NAC is not fully elucidated. We investigated the change in expression of PAMIP1, the gene encoding for the pro-apoptotic protein, NOXA, following NAC in two breast cancer gene dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Of these, the most robust evidence arises from studies that measured multiple senescence-associated markers simultaneously, which is suggested by ChatGPT as a methodological necessity in this response. For example, a three-marker signature of Lamin B1, Ki67, and p16 INK4a , showed that TIS is evident in roughly 40% of breast tumor samples exposed to neoadjuvant chemotherapy (Al Shboul et al, 2023;El-Sadoni et al, 2023). It is logical that this approach was missed by ChatGPT due to its availability only after the last update of the AI platform.…”
Section: P16mentioning
confidence: 99%
“…Of these, the most robust evidence arises from studies that measured multiple senescence-associated markers simultaneously, which is suggested by ChatGPT as a methodological necessity in this response. For example, a three-marker signature of Lamin B1, Ki67, and p16 INK4a , showed that TIS is evident in roughly 40% of breast tumor samples exposed to neoadjuvant chemotherapy (Al Shboul et al, 2023;El-Sadoni et al, 2023). It is logical that this approach was missed by ChatGPT due to its availability only after the last update of the AI platform.…”
Section: P16mentioning
confidence: 99%
“…A wide range of chemotherapeutic drugs has been reported to induce senescence in vitro in breast cancer cells, such as doxorubicin, etoposides, irinotecan, methotrexate, paclitaxel, cisplatin, 5-fluorouracil and palbociclib [8][9][10][11][12][13]. Moreover, the induction of senescence has been detected in tumour tissues of breast cancer patients after receiving chemotherapy, indicating that senescence is a clinically relevant response to cancer therapy [14][15][16][17]. In early experiments, therapy-induced senescence (TIS) was considered to have a beneficial function in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%